Clinical features of childhood diabetes mellitus focusing on latent autoimmune diabetes - Seung Ho Lee; Jeesuk Yu (Korean Society of Pediatric Endocrinology, 2016)
PurposeThis study was designed to evaluate the clinical characteristics of childhood diabetes mellitus (DM) according to its classification as well as the clinical course of latent autoimmune diabetes (LAD) that initially showed noninsulin dependence despite autoantibody positivity.MethodsA total of 91 subjects diagnosed between 2001 and 2015 were enrolled in the study. They were classified into 3 groups: type 1 DM, LAD, and type 2 DM. Clinical features and laboratory findings were compared among groups.ResultsAmong 91 subjects, type 1 DM, LAD, and type 2 DM were 51 (56.0%), 7 (7.7%), and 33 (36.3%), respectively. In LAD, age at diagnosis and BMI Z-scores were higher, as compared with those in type 1 DM. Initial serum c-peptide levels were higher in LAD than those in type 1 DM, but lower than those in type 2 DM. In LAD, the mean follow-up duration was 4.56 years, and 43% of the patients ultimately required intensive insulin treatment with dosage of > 0.5 U/kg/day. HbA1C and serum c-peptide levels at the time of intensive insulin treatment were 9.43±0.93% and 1.37±1.36 ng/mL, respectively. Recent serum c-peptide/glucose ratio was lower in the group requiring intensive insulin treatment than the group without intensive insulin treatment, with P-value of 0.057 (0.003±0.005 vs. 0.071±0.086).ConclusionInitial autoantibody evaluation is useful for classification and management. Close monitoring of the patients with LAD is important due to the expected need for intensive insulin treatment within several years.